THE LEARNING DESIGN TO IMPROVE THE LEARNING OUTCOMES ON THE ELECTRICAL CIRCUIT TOPIC - Ragustini Ragustini; Rizki Zakwandi; Teguh Gumilar; Rafhi Febryan Putera (Journal of Teaching and Learning Physics, 2022)
This study aims to determine the implementation of the project-based learning process on electrical energy topic in class VI and the improvement of student learning outcomes in science learning on electrical energy topic. This research was conducted on students of class VI with a total of 29 students consisting of 13 males and 16 females. There were three times of data collection in this study which included Pre-Cycle, Cycle 1, and Cycle 2. The results showed that the active involvement of students in learning activities could increase their understanding of the subject matter being taught. In addition, project-based learning by making series and parallel circuits in the implementation of making traffic lights makes students more enthusiastic and active in learning.